ANALISIS IMPLEMENTASI APLIKASI MOBILE SYSTEM PADA SISTEM INFORMASI MANAJEMEN DI RUMAH SAKIT UMUM DAERAH (RSUD) BUDHI ASIH - Safitri, Annisa Apriani; Mustakim, Mustakim (UI Scholars Hub, 2024)
Hospital Information System (HIS) or Hospital Management Information System (SIMRS) is important in supporting the entire hospital process through information technology. Budi Asih Regional Hospital has a Hospital Information System in its management but still has various issues and challenges in its implementation. This study uses qualitative methods, informant selection with purposive sampling, and data collection techniques through in-depth interviews, observations, and document analysis. Information systems are part of organizational resources for decision-making regarding leadership needs. The Management Information System must be designed by considering data architecture including automated codification in an integrated manner such as statistics, mapping for further management that plays a role in all hospital service functions ranging from queue management, registration, discharge patient services, and other hospital service processes. The concept of a clinical information system is an interaction between patients and health workers in the context of service. Information data issued by the Hospital Information System unit is related to increasing the effectiveness of services and improving health services. Aspects that must be considered in the development of a Hospital Information System, such as hardware, software, and network devices, which must constantly be developed, maintained, and maintained periodically to provide convenience in producing information data for hospital management to determine policies taken by management in improving health services.